DEVELOPMENT OF YIELD AND QUALITY OF WINTER WHEAT VARIETIES USING TIMAK AGRO FERTILIZERS - Шакалій, Світлана; Маренич, Микола; Скубій, А.; Литвиненко, Т.; Шевченко, В. (SWorldJournal, 2023)
An integral indicator of the effectiveness of agrotechnical measures is the yield of agricultural crops, which is formed under the influence of specific soil and climatic conditions and elements of growing technology, which determine the productivity of p